Longitudinal trajectories of mental health problems and their association with reoffending in a Dutch pre-trial prison cohort - Weber, Michael; Baggio, Stéphanie; Gonçalves, Leonel C.; Nieuwbeerta, Paul; Dirkzwager, Anja J. E. (Frontiers in Psychiatry, 2022)
The burden of mental health problems in detained persons is high. At the same time, mental health problems are discussed as possible predictors for criminal recidivism. During detention, mental health tends to improve. The aims of the study were twofold: First, to identify group-based trajectories of mental health problems over the course of detention; second, to test the association between trajectories and criminal recidivism. A prospective cohort of 1,904 adult males detained in Dutch pre-trial detention facilities was assessed at three time points after imprisonment (week 3, month 3, and month 9). Mental health problems were measured using the Brief Symptom Inventory. Recidivism was defined as reconviction and re-incarceration up to 18 months post-release. We used group-based trajectory modeling and logistic regressions for the analyses. On average, self-reported mental health improved during incarceration. Two distinct groups of mental health trajectories were identified: The majority (81%) reported relatively low levels of mental health problems, remaining stable over time. A small group (19%) reported high distress after prison entry with improvements over time. Older age, pre-existing functional impairment due to alcohol or drug use, diagnosis of psychiatric disorders, debts, use of psychiatric care during detention, and a more severe experience of detention were associated with membership in the second group. Group membership did not predict reoffending. The study confirms prior findings illustrating a general positive change in mental health symptoms during detention. The course of mental health was associated to pre-existing socio-demographic and psychological characteristics that seem worth to be considered in correctional treatment plans. Changes in mental health did not result in better legal outcomes. An interesting avenue for future research would be to examine changes in specific mental health symptoms or disorders in relation to recidivism risk.